Correlation between the peripheral neuropathy and levels of hs-CRP, IL-1β and IL-6 in senile Parkinson’s disease patients - Zhang, Yongzhi; Liu, Yihan; Li, Yanmin; Zhang, Sai; Yuan, Xiaoyang; Liu, Chenfei; Geng, Lijuan; Gu, Ping (Cellular and Molecular Biology, 2023)
This study was carried out to investigate the correlation between the onset of peripheral neuropathy and levels of hypersensitive C-reactive protein (hs-CRP), interleukin 1β (IL-1β) and IL-6 in senile Parkinson's disease (PD) patients. For this purpose, a total of 60 PD patients and 60 age-matched healthy subjects were enrolled in this study and received the assessment for peripheral nerves by using the quantified method. Besides, levels of hs-CRP, IL-1β and IL-6 in serum were determined to analyze the correlation between the clinical features, including the severity of PD and cognitive decline, and the levels of hs-CRP, IL-1β and IL-6. Results showed that PD patients had more cases of peripheral neuropathy than those in the healthy control group. Levels of hs-CRP, IL-1β and IL-6 in the serum of PD patients were much higher than those in the healthy control (P<0.05). Besides, PD patients had lower scores of MMSE and MoCA but higher CNPI scores when compared to the healthy control group. As a result, we found that the severity of peripheral neuropathy was in a positive correlation with the levels of hs-CRP, IL-1β and IL-6. It was concluded that PD patients generally have peripheral neuropathy that may correlate with the increases in the levels of hs-CRP, IL-1β and IL-6, and early intervention may mitigate the development and progression of peripheral neuropathy.